2021
DOI: 10.1002/ehf2.13573
|View full text |Cite
|
Sign up to set email alerts
|

Clinical presentation and long‐term outcomes of infantile hypertrophic cardiomyopathy: a European multicentre study

Abstract: AimsChildren presenting with hypertrophic cardiomyopathy (HCM) in infancy are reported to have a poor prognosis, but this heterogeneous group has not been systematically characterized. This study aimed to describe the aetiology, phenotype, and outcomes of infantile HCM in a well-characterized multicentre European cohort. Methods and resultsOf 301 children diagnosed with infantile HCM between 1987 and 2019 presenting to 17 European centres [male n = 187 (62.1%)], underlying aetiology was non-syndromic (n = 138,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 29 publications
(12 citation statements)
references
References 31 publications
0
12
0
Order By: Relevance
“…Prediction of clinical outcomes for patients with HCM is challenging because of the substantial heterogeneity of the population, particularly in children. Several registries have investigated the outcomes for HCM with different etiologies [18][19][20][21][22] and demonstrated that patients with RASopathies carry a higher risk of death or heart transplantation compared with idiopathic or sarcomeric HCM. Wilkinson et al 21 reported that patients with NS and HCM have a worse risk profile at presentation compared with other children with HCM, resulting in a 1-year mortality of 22%.…”
Section: Discussionmentioning
confidence: 99%
“…Prediction of clinical outcomes for patients with HCM is challenging because of the substantial heterogeneity of the population, particularly in children. Several registries have investigated the outcomes for HCM with different etiologies [18][19][20][21][22] and demonstrated that patients with RASopathies carry a higher risk of death or heart transplantation compared with idiopathic or sarcomeric HCM. Wilkinson et al 21 reported that patients with NS and HCM have a worse risk profile at presentation compared with other children with HCM, resulting in a 1-year mortality of 22%.…”
Section: Discussionmentioning
confidence: 99%
“…Infants with pathologic hypertrophy are often associated with inborn errors of metabolism, which confers a significantly increased risk of death. 19 It could be possible that variants in pathways associated with metabolic disorders could be another example. In addition, genetic variants of α‐protein kinase 3 have been implicated as a pediatric cardiomyopathy gene.…”
Section: Part I: Emerging Knowledge Of the Genetics Of Hcmmentioning
confidence: 99%
“…Presentation in infancy (<1 year of age) was associated with an increased risk of cardiovascular death 5,6,8,83,84 ; however, the cause of death in this subgroup is most commonly associated with congestive heart failure and non-cardiovascular causes, rather than sudden cardiac death. 85 One study reported an increased risk of sudden cardiac death or malignant arrhythmia occurring in children above 13 years of age, 24 and a population-based study showed that 8-16-year-olds had a significantly higher mortality rate in sudden cardiac death than 17-30-year-olds, with the highest rate between the ages of 9 and 14 years. 44 Maurizi et al 22 evaluated 100 hypertrophic cardiomyopathy patients from 1 to 16 years old at diagnosis to describe the long-term outcome of paediatric onset hypertrophic cardiomyopathy and to identify agespecific arrhythmic risk factors.…”
Section: Electrocardiogram Phenotype and Electrocardiogram Risk Score...mentioning
confidence: 99%